2022
DOI: 10.51339/nisbah.v3i1.345
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Literasi Keuangan Syariah, Religiusitas Dan Persepsi Mahasiswa Jabodetabek Terhadap Keputusan Menggunakan Layanan Perbankan Syariah

Abstract: The Islamic banking industry has long been awaited by all Muslim communities who want a banking system based on sharia principles in Indonesia. Even though Islamic banks are now present, there are still many dynamics faced by Islamic banking. This study aims to describe the influence of Islamic financial literacy, religiosity and perceptions of Jabodetabek students on decisions to use Islamic banking services. The research method used in this research is quantitative with data collection method using purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Selain itu perlu juga mensosialisasikan terkait akan pentingnya literasi keuangan syariah bagi anak-anak muda dan lainnya (Falevy, Suryani, and Priyatno 2022), dimana dewasa ini di zaman yang serba digital perlu pengembangan produk pada perbankan syariah agar mampu bersaing dengan perbankan konvensional, seperti halnya digitalisasi pada zakat (Ahyani, Yuliani, et al 2022). Dan yang tidak kalah penting adalah Pengelolaan dana Bank Syariah, dimana ini merupakan upaya untuk mengarahkan posisi dana yang diterima bank syariah dari kegiatan mengumpulkan dana menyalurkan dana dalam bentuk pembiayaan sehingga bank syariah tetap mampu memenuhi kriteria-kriteria likuiditas, rentabilitas dan solvabilitas (Mulyani and Jamilah 2022).…”
Section: Eksistensi Filsafat Ekonomi Syari'ah Sebagai Landasan Filoso...unclassified
“…Selain itu perlu juga mensosialisasikan terkait akan pentingnya literasi keuangan syariah bagi anak-anak muda dan lainnya (Falevy, Suryani, and Priyatno 2022), dimana dewasa ini di zaman yang serba digital perlu pengembangan produk pada perbankan syariah agar mampu bersaing dengan perbankan konvensional, seperti halnya digitalisasi pada zakat (Ahyani, Yuliani, et al 2022). Dan yang tidak kalah penting adalah Pengelolaan dana Bank Syariah, dimana ini merupakan upaya untuk mengarahkan posisi dana yang diterima bank syariah dari kegiatan mengumpulkan dana menyalurkan dana dalam bentuk pembiayaan sehingga bank syariah tetap mampu memenuhi kriteria-kriteria likuiditas, rentabilitas dan solvabilitas (Mulyani and Jamilah 2022).…”
Section: Eksistensi Filsafat Ekonomi Syari'ah Sebagai Landasan Filoso...unclassified
“…The Financial Services Authority (OJK) defines financial literacy as knowledge, skills, and beliefs that influence attitudes and behavior to improve the quality of decision-making and financial management to achieve prosperity. Meanwhile, Falevy et al (2022) stated that Islamic financial literacy is a person's skills, actions, capabilities, and competencies in managing financial resources under Islamic sharia principles. Based on the above understanding, it can be said that Islamic financial literacy is a fundamental part of the life of the Muslim community.…”
Section: Islamic Financial Literacy On Financial Decisionsmentioning
confidence: 99%
“…Research conducted by Munardi et al (2020) and Falevy et al (2022) uncovered that Islamic financial literacy positively and significantly affected decisions to use Islamic banking services. Thohari and Hakim (2021) also found that Islamic financial literacy positively and significantly impacted saving decisions in Islamic banks.…”
Section: Islamic Financial Literacy On Financial Decisionsmentioning
confidence: 99%